2007
DOI: 10.1097/00002820-200701000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use in Pediatric Oncology Patients in Eastern Turkey

Abstract: The use of complementary and alternative medicines (CAM) among children with cancer is becoming increasingly popular. Therefore, it is important to gain insight into the prevalence and factors related to the use of CAM. This study presents findings from a study of parents of 88 children with cancer who were receiving or had received conventional therapy for treatment of childhood cancer at a pediatric oncology unit in eastern Turkey. The findings indicated that 48.9% of the respondents reported the use of 1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
7
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 27 publications
3
53
7
7
Order By: Relevance
“…This percentage of users is comparable with a recent study by Clerici et al 24 who showed that 12.4% of children suffering from neoplastic diseases in Italy used at least one kind of CAM therapy since their diagnosis. However, this is lower than estimates in other studies carried out in the United States, 29 Turkey, 30 and Malaysia. 6 Methodological, cultural, and definitional differences might explain this variation.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This percentage of users is comparable with a recent study by Clerici et al 24 who showed that 12.4% of children suffering from neoplastic diseases in Italy used at least one kind of CAM therapy since their diagnosis. However, this is lower than estimates in other studies carried out in the United States, 29 Turkey, 30 and Malaysia. 6 Methodological, cultural, and definitional differences might explain this variation.…”
Section: Discussioncontrasting
confidence: 64%
“…All parents denied any side effects of the CAM therapy used, which, similar to other studies, reflects the perception of some parents that the CAM used is safe and effective. 30,38 Our results indicated that strengthening immunity and improving the chance of cure were the main reasons behind the use of CAM. This finding is in accordance with the results of other studies in Germany 25 and in Canada.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other studies also reported hopelessness of parents, especially mothers of children with cancer (15-17). Despite existing available tools for discovering hopelessness (18), it can be discovered through daily communication with the parents of a child with cancer, by their expressing negative feelings about what would be happen in the future for their child. It has been shown that social support can cause less disappointment and hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos pais entrevistados manifestou necessidade de obter informação vinda da equipe médica, além de um canal aberto para uma comunicação sobre esse tipo de terapêutica. Os profissionais de saúde devem permanecer informados sobre os benefícios e os efeitos adversos das TAC para discutir as opções de tratamento com os pacientes e suas famílias e para monitorar a sua eficácia (ELIAS, 2006;FLETCHER, 2004;GENTIL, 2010;;GOZUM, 2007;HAMIDAH, 2009;MCCURDY, 2003;MOLASSIOTIS, 2004;NDAO, 2013;O'CONNOR, 2013; Metade dos estudos incluídos nesta revisão mostraram que a maior parte dos pais ou cuidadores não revelou ou discutiu sobre o uso do TAC com os profissionais de saúde envolvidos no tratamento oncológico da criança ou adolescente (AL- QUDIMAT, 2010;ELIAS, 2006;GENC, 2009;GENTIL, 2012;GÓMEZ-MARTÍNEZ, 2007;GOZUM, 2007;KARADENIZ, 2007;O'CONNOR, 2013;LIM, 2006;NAJA, 2011;WEYL, 2006). Somente em um dos estudos incluídos na revisão, os participantes ficaram divididos entre revelar e não revelar sobre uso do TAC, ou seja, 50% referiram discutir com os profissionais sobre o assunto enquanto que a outra metade não o fizeram (NDAO, 2013).…”
Section: B) Motivações Para a Busca Dos Tratamentos Alternativos E Counclassified